HABITUATION METHOD IN FORMING ISLAMIC CHARACTER IN GENERATION Z STUDENT AT SMPI BINA UMAT BABELAN BEKASI - Vemmi Kesuma Dewi Raden Roro; Awafiya Ulya (Al Aqidah (Jurnal Studi Islam), 2024)
INSTILLING CHARACTER EDUCATION BY HABITUATION. Character education is education which not only teaches what is good and bad, but also teaches children to feel these values and be able to do it. Habit is one of the effective ways in the process of forming children's character. Habits are attitudes and behaviors that are relatively permanent and automatic through an iterative learning process. Good habits will also have a good impact on children for the future. This study aims to determine what biases are carried out in SMPI Bina Umat in instilling Early Childhood Character education. This research is a field research with a qualitative descriptive approach. The results of the research show that character education is carried out every day through habituation which is carried out regularly. In their religious development, SMPI Bina Umat children are always accustomed to reading Asmaul Husna and together chanting the part of Quran every day. The development of social care is manifested in the Friday practice and the practice of Ramadan. Eating together and sharing supplies are also a means of cultivating character education for children, namely developing a sense of empathy, discipline, independence, social care, responsibility. The main purpose of the habituations is to build the character of children with noble character, moral character, having good manners, and good habits.